2015
DOI: 10.1128/aem.03867-14
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Internalization of Animal Caliciviruses via the Roots of Growing Strawberry Plants and Dissemination to the Fruit

Abstract: Human norovirus (NoV) is the leading cause of foodborne disease in the United States, and epidemiological studies have shown that fresh produce is one of the major vehicles for the transmission of human NoV. However, the mechanisms of norovirus contamination and persistence in fresh produce are poorly understood. The objective of this study is to determine whether human NoV surrogates, murine norovirus (MNV-1) and Tulane virus (TV), can attach and become internalized and disseminated in strawberries grown in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Metagenomic analysis of romaine and iceberg lettuce has shown the presence of wide range of plant and animal/ human viruses already on the field [63•]. It has also been shown that NoV can be internalised by some plants such as lettuce and strawberries through the root system and can therefore be present inside the plant and fruits rather than just contaminating the surface [64,65]; similar to the internalisation and retention of acid resistant viruses in water filtering molluscs [66]. Even though being internalised, NoV, such as most animal and human viruses, is not able to infect or replicate in plant cells [67].…”
Section: Other Food-contaminating Virusesmentioning
confidence: 99%
“…Metagenomic analysis of romaine and iceberg lettuce has shown the presence of wide range of plant and animal/ human viruses already on the field [63•]. It has also been shown that NoV can be internalised by some plants such as lettuce and strawberries through the root system and can therefore be present inside the plant and fruits rather than just contaminating the surface [64,65]; similar to the internalisation and retention of acid resistant viruses in water filtering molluscs [66]. Even though being internalised, NoV, such as most animal and human viruses, is not able to infect or replicate in plant cells [67].…”
Section: Other Food-contaminating Virusesmentioning
confidence: 99%
“…) and strawberry (DiCaprio et al . ) confirming that the use of faecally contaminated soil may pose a risk to the safety of some ready‐to‐eat products.…”
Section: Discussionmentioning
confidence: 81%
“…Third, the persistence of viruses in produce could be due to the small size of the virus, which would allow them to enter small crevices and spaces on the produce surface and hence be protected from removal or inactivation (Wei et al, 2010). Finally, viruses may be internalized via roots and/or leaves, and disseminated to other portions of the plants which would render traditional sanitization strategies ineffective against internalized viruses (DiCaprio et al, 2015;Dicaprio et al, 2012;Esseili, Wang, Zhang, et al, 2012;Hirneisen and Kniel, 2013;Wei et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 95%